Indium bump array fabrication on small CMOS circuit for flip-chip bonding - 黄寓洋 张宇翔 殷志珍 崔国新 刘惠春 边历峰 杨辉 张耀辉 (Journal of semiconductors, 2011)
We demonstrate a novel method for indium bump fabrication on a small CMOS circuit chip that is to be flip-chip bonded with a GaAs/A1GaAs multiple quantum well spatial light modulator. A chip holder with a via hole is used to coat the photoresist for indium bump lift-off. The 1000 μm-wide photoresist edge bead around the circuit chip can be reduced to less than 500 μm, which ensures the integrity of the indium bump array. 64 - 64 indium arrays with 20 μm-high, 30 μm-diameter bumps are successfully formed on a 5 - 6.5 mm^2 CMOS chip.